HUBUNGAN PENGETAHUAN DAN SIKAP IBU TENTANG MAKANAN PENDAMPING ASI DENGAN KEJADIAN DIARE PADA BAYI DAN BALITA DI WILAYAH KERJA PUSKESMAS TANJUNG SATAI KABUPATEN KAYONG UTARA - ., Sulastri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: High incidence of diarrhea in infants and toodlers isinfluenced by various factors, one of them is the incorrect feeding practicecaused by mother’s knowledge and attitude. Objectives: To know thecorrelation between mother’s knowledge and attitude aboutcomplementary feeding with the incident of diarrhea in infants andtoodlers. Methods: This study was an analytic study with cross sectionalapproach. Samples were taken for 48 mothers at working area of TanjungSatai primary health centre in Kayong Utara. Result: The result ofbivariate analyze by Fisher test show that mother’s knowledge hadcorrelation with the incident of diarrhea in infants and toodlers withp=0,004. Attitude had correlation with the incident of diarrhea in infantsand toodlers with p=0,048. Conclusion: There is a significant correlationbetween mother’s knowledge and attitude about complementary feedingwith incident of diarrhea in infants and toodlers.Key words: diarrhea, knowledge, attitude, complementary feeding1)Faculty of Medicine, Tanjungpura University, Pontianak, KalimantanBarat2)Department of Community Medicine, Faculty of Medicine,Tanjungpura University, Pontianak, Kalimantan Barat3)Department of Pediatric, Faculty of Medicine, TanjungpuraUniversity, Pontianak, Kalimantan Barat